Potential distribution of ecosystems in the Southern Zone of Ecuador: modeling from a correlative approach - Poma-Sarango, Marco Antonio; Poma-Sarango, Diego; Guaman, Lizbeth; Guillermo Chuncho, Carlos; Juela, Oscar; Benavidez-Silva, César (Revista de Estudios Andaluces, 2024)
Climate change is one of the factors affecting terrestrial ecosystems through global climate variability, and by acting synergistically with other stressors, its effects on ecosystems are enhanced, potentially directly affecting biological diversity. Consequently, we have analyzed the potential distribution of ecosystems in the Southern Zone of Ecuador under a future climate change scenario (RCP 6.0 2080), which is ecologically, socially, and economically important for populations surrounding the ecosystems. To do this, we used potential distribution models (SDM) implemented in Biomod2 4.0, which uses a set of relevant methods and tools for dealing with a series of methodological uncertainties related to distribution modeling, as well as the ability to quickly build individual models or combine them in different ways through ensembles, relating biophysical variables (topographic and climatic) with the presence/absence points of ecosystems in the Southern Zone. The results indicate that the temperature would increase for all ecosystems, while precipitation in some high-altitude ecosystems, such as Paramo and Montane Forest, would decrease, unlike what would happen with other ecosystems at lower altitudes, where precipitation would show an increase (and, in the rest of the ecosystems, in general, it would show an increase). This climate variability may generate new climate configurations and ecosystems may tend to shrink or expand in response, changing their distribution range.